Is the internal connection more efficient than external connection in mechanical, biological, and esthetical point of views? A systematic review - Goiato, Marcelo Coelho [UNESP]; Pellizzer, Eduardo Piza [UNESP]; Silva, Emily Vivianne Freitas [UNESP]; Bonatto, Liliane da Rocha [UNESP]; Santos, Daniela Micheline dos [UNESP] (Springer, 2015)
This systematic review aimed to evaluate if the internal connection is more efficient than the external connection and its associated influencing factors. A specific question was formulated according to the Population, Intervention, Control, and Outcome (PICO): Is internal connection more efficient than external connection in mechanical, biological, and esthetical point of views? An electronic search of the MEDLINE and the Web of Knowledge databases was performed for relevant studies published in English up to November 2013 by two independent reviewers. The keywords used in the search included a combination of dental implant and internal connection or Morse connection or external connection. Selected studies were randomized clinical trials, prospective or retrospective studies, and in vitro studies with a clear aim of investigating the internal and/or external implant connection use. From an initial screening yield of 674 articles, 64 potentially relevant articles were selected after an evaluation of their titles and abstracts. Full texts of these articles were obtained with 29 articles fulfilling the inclusion criteria. Morse taper connection has the best sealing ability. Concerning crestal bone loss, internal connections presented better results than external connections. The limitation of the present study was the absence of randomized clinical trials that investigated if the internal connection was more efficient than the external connection. The external and internal connections have different mechanical, biological, and esthetical characteristics. Besides all systems that show proper success rates and effectiveness, crestal bone level maintenance is more important around internal connections than external connections. The Morse taper connection seems to be more efficient concerning biological aspects, allowing lower bacterial leakage and bone loss in single implants, including aesthetic regions. Additionally, this connection type can be successfully indicated for fixed partial prostheses and overdenture planning, since it exhibits high mechanical stability.
Keywords: Dental implants; Connection; Biomechanical phenomena; Systematic review